(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A solar heat exposure or solarization trial was carried outduring November 2007 at Shambat Research Station, Sudan. TheObjective of the study was to control the date moth Ephestia calidella(Guen.) and the saw-toothed grain beetle Oryzaephilus surinamensis (L.)in stored dates. Black iron and polyethylene solar heat collectors wereconstructed and exposed to the sun. The results showed considerablevariation in the mean temperature between the iron heat collector,polyethylene heat collector and control treatments; they were 41.5C,53.7C and 57.4C, respectively, while the ambient mean temperature andrelative humidity were 33C and 52.9%. Six and 12 hours were enoughto control E. calidella in the iron heat and polyethylene heat collectors,respectively, and 18 and 24 hours to control O. surinamensis. Exposingthe ripened dates to a mean temperature of 57.4C for 24 hours did notlead to high significant change in the chemical composition, except thatsome sucrose was inverted to reducing sugars.